Deratization Activities in the Jewish Autonomous Region in the Post-Flooding Period - V. A. Yanovich; E. S. Mironenko; I. S. Butenko; P. V. Kopylov; I. P. Snetkova; N. P. Shestopalov; A. D. Vorontsova; M. A. Tarasov; V. M. Rusakov (Проблемы особо опасных инфекций, 2014)
Represented is a quantitative characteristic of the objects and facilities in the Jewish Autonomous Region exposed to the flooding-2013. Justified is the necessity for implementation of preventive measures against increase in the activity of HFRS natural foci; showed are the data on disinfestation organization for the prevention of natural-focal infection during the high water and post-flooding period in 2013. Displayed are the results of deratization efficacy control in various administrative units of the entity, calculated using Abbot formula, as well as results of investigation of small rodent population density at the natural stations and substantiation of the barrier disinfestation carrying out. Specified are the areas of the continuous and barrier disinfestation, indicators of Hanta Virus contamination of the rodents caught while performing control over efficacy of deratization works.